Penguatan Kompetensi Guru TPQ, TPSQ, dan Tahfizh Melalui Program Pelatihan Terpadu Di Kenagarian Kandang Baru, Kabupaten Sijunjung - Warlan Sukandar (Lembaga Penelitian, Penerbitan dan pengabdian kepada masyarakat (LP3M) STIT Al-Urwatul Wutsqo Jombang., 2025)
The integrated training program for TPQ, TPSQ, and Tahfizh teachers in Kenagarian Kandang Baru, Sijunjung Regency, was designed to address the low pedagogical competence, teaching skills, and classroom management capabilities among Qur’anic educators. The three-day training involved 23 participants and used a comprehensive approach combining theoretical knowledge and hands-on practice. The training modules included teaching by heart, TPQ management, effective Qur’anic teaching strategies, as well as reinforcement of tajwid and tahsin. Evaluation results indicated that 90% of participants significantly improved their understanding of child-centered teaching methods and were able to apply more engaging and enjoyable tahfizh approaches. Moreover, 83% of participants demonstrated the ability to integrate talaqqi, tikrar, and educational games into their teaching practices. The program also encouraged strong commitment from the local government to continue the initiative through follow-up training and ongoing monitoring. Collaboration between educators and local authorities was directed toward establishing a sustainable learning community to foster an adaptive and high-quality Qur’anic education ecosystem. This initiative serves as a promising model of locally rooted teacher empowerment that could be replicated in other regions seeking to strengthen non-formal Islamic education institutions.